Sistemas de preparo do solo associado à diferentes lâminas de irrigação na cultura do milho - Reis, Maria Albertina Monteiro dos (2018)
The green corn production even though little explore create higher income that the grain corn production, this occurs to the bigger value of the commercialized product (ears), besides allow later plant exploitation for the animal alimentation or soil cover. The water is a limiting factor for the plants development, principally in dry regions, being necessarily studies for the better use of water resources in these regions. The goal of this study is to evaluate the production of green corn and silage in three tillage systems associated to five depths of irrigation. The evaluations were realized in the agricultural experimental area belonging to the Department of Agricultural Engineering of the University Federal of Ceará (UFC – Campus of Pici), for two production cycles (07/04/2017 – 05/07/2017 and 29/08/2017 – 20/11/2017). The treatments were made by three tillage systems, P1 – conventional tillage (plough + harrow), P2 – chisel plow and P3 – no tillage and five depths of irrigation based on the crop evapotranspiration L1 – 25%, L2 – 50%, L3 – 75%, L4 – 100% and L5 – 150%. The experimental design used was randomized blocks (DBC), in a 3x5 factorial arrangement in four replications, resulting in 60 treatments. The evaluated were the operational performance of the set tractor-seeder (displacement speed, wheels slippage, consumption and operational capacity), the agronomic/phytotecnyc performance of the corn and the economic viability of treatments. The data was submitted to an analysis of variance and when significant was submitted to a 5% of probability Tukey for qualitative variables and regression analysis for quantitative variables. It was concluded that to the studied conditions the conventional tillage provide better operational performance of the set tractor-seeder with higher displacement speed and higher operational field capacity. The depth irrigation of 25% to the evapotranspiration provide higher water use efficiency, obtained more production with less water volume applied. The better economic viability at first production cycle was obtained in tillage system of chisel plow associated to depth of 25% of ETc and at the second cycle it was in no tillage system associated to depth of 150% of ETc.